ANAPLASTIC THYROID CARCINOMA 10 YEARS FOLLOWING PAPILLARY THYROID CARCINOMA: A CASE REPORT OF MIXED HISTOMORPHOLOGY AND DIAGNOSTIC CHALLENGE - Grace Durham; Cindy Almaraz; Corey Steinman; Phillip Pearson; Mohamed Aziz; Jessica Jahoda (World Journal of Biology Pharmacy and Health Sciences, 2026)
Anaplastic thyroid carcinoma (ATC) is a rare, highly aggressive thyroid malignancy associated with rapid progression, diagnostic complexity, and poor prognosis, particularly true when arising through dedifferentiation of pre-existing papillary thyroid carcinoma (PTC). We present the case of a 63-year-old female with a history of papillary thyroid carcinoma (PTC) previously treated with total thyroidectomy and radioactive iodine ablation 10 years prior. She presented with a rapidly enlarging anterior neck mass, progressive dysphagia, hoarseness, and intermittent stridor. Imaging revealed a locally invasive necrotic mass with intense hypermetabolic activity. Histopathological examination demonstrated mixed histomorphologic features, including spindle cell, squamous, and clear cell differentiation, while subsequent molecular analysis identified BRAF V600E and TERT promoter mutations. Together, these findings supported the diagnosis of anaplastic thyroid carcinoma. Guided by a multidisciplinary tumor board, the patient underwent tracheostomy, palliative radiotherapy, and targeted therapy with dabrafenib and trametinib. However, despite initial stabilization, the patient died of progressive disease nine months after diagnosis. This case illustrates how a decade-long latency, mixed histomorphology, and a high-risk molecular profile can complicate the recognition of anaplastic transformation. It underscores the diagnostic and therapeutic pathway required for optimal management.